Revitalization of Tourism Village Facilities as an Effort to Increase Income and Sustainability - Andika, Andika; Amara, Raihan; Lizza Thania Meder, Villa; Rahma Sari, Melniya; Klau Seran, Kondradus; Nur Prasetya, Arvin; Dhiani Irdi, Trissa; Umalekhoa, Yotita; Riyanto, Alex; Yoga Pranata, Tri; Syam Hidayat, Ahmad; Irawan Subandrio, Erik (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Developing village tourism in Indonesia is a crucial government strategy to boost the local economy and increase regional income. Villages with diverse assets such as natural beauty, rich cultural traditions, traditional cuisine, handicrafts, and historical sites have the potential to become attractive tourist destinations. This research focuses on Gunung Wangi Nature Tourism, which offers attractions such as sunset views, city lights at night, and camping activities. However, constraints such as inadequate facilities and infrastructure are the main focus of this research. Through a Community-Based Participatory Research (CBPR) approach, this research offers solutions to revitalize the facilities and infrastructure and a long-term revitalization strategy to increase the attractiveness of Gunung Wangi. Local community involvement is integrated into every research stage, including problem identification, Focus Group Discussion (FGD), implementation, and evaluation. Revitalization efforts at Gunung Wangi Nature Park have shown positive results, with substantial improvements reported in post-revitalization evaluations. Feedback from stakeholders, including visitors, MSME players, and Gunung Wangi Tourism village managers, showed significant improvements in infrastructure and visitor experience. While a few respondents suggested room for improvement, the overall success is evident in the increase in visitor numbers, with the majority experiencing a significant increase. This revitalization has rejuvenated this tourist spot's attractiveness and boosted economic growth in the local community